Russia and European Countries: Statistical Assessment of Differences in the Level of Gender Differentiation - Oksana N. Komar (Современная Европа)
The article provides a comprehensive statistical assessment of the level of gender differentiation in Russia and European countries. A consolidated rating of the level of gender differentiation has been developed, calculated as the sum of a country's ranks in three indices: gender inequality (GII), gender social norms (GSNI) and Women, Business and the Law (WBL). The countries have been ranked based on this rating. An in-depth analysis of the constituent elements of each index was made. The positions of the Russian Federation were compared with those of the European countries, leading in the ranking. The main sources of information for the calculations were the statistical data of the United Nations, the World Bank, and the demographic statistics of Rosstat. It has been established that the Russian Federation should strengthen legal protection in the field of gender. Measures have been proposed to help reduce gender inequality. They have been tested on the basis of a quantitative assessment of the forecast level of the Women, Business and Law index for the Russian Federation.